Bionanoelectronics Bioinquiring and Bioinspired Devices - Dragoman, Daniela; Dragoman, Mircea; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book presents the achievements in bionanoelectronics in a coherent manner. It deals with nanodevices applied to biostructures, molecular motors, molecular pumps, molecular nanoactuators and electronic biodevices, including nanodevices for sensing and imaging biomolcules. The book describes bionanoelectronics, detection of biomolecules and targets various biological applications such as detection and sequencing of DNA and early detection of various deseases and nanomedicine. Further important topics of the book are biomimetics and bioinspired electronics.The book also deals with biomolecules as building blocks of nanodevices for nanoelectronics or future computing architecture The application of scanning probe techniques to biological samples is described.
Fundamentals on bionanotehnologies -- Sensing of biomolecules -- Imaging and manipulation of biomolecules -- Biomolecular architectures -- Molecular devices -- Biocomputing -- Nanomedicine -- Bioinspired devices.
Keywords: Physics; Chemistry, Physical organic; Engineering; Nanotechnology; Physics; Nanoscale Science and Technology; Nanotechnology and Microengineering; Nanotechnology; Biophysics and Biological Physics; Physical Chemistry